(untitled) (Vietnam Journal of Community Medicine, 2021)
Objective: To survey the use of carbapenem antibiotics at Can Tho Children’s Hospital. Objects and methods: Retrospective-descriptive study on 140 medical records of patients being treated at departments of Can Tho Children’s Hospital during the period from June 1st, 2020 to December 31st, 2020. Results: 26.43% of carbapenems were indicated empirically initiate, 73.57% of carbapenem was indicated in alternative regimens as the presence of microbiological results or worsened or impaired patient status. Carbapenem was mainly used in combination regimens. The proportion of the combination in the initiation regimen was 100%. In which, the proportion of combination regimen between carbapenem and an antibiotic (or vancomycin or gentamicin) was mainly. The rate of combination of three antibiotics was 18.9%. In the replacement regimen, the proportion of combination regimen was 79.6%. Of these, 57.3% of the carbapenem was combined with another antibiotic, most of which was combined with vancomycin. Combination regimen of three or four antibiotics accounted for a low percentage. Conclusion: 26.43% of carbapenem was indicated empirically initiate, 73.57% of carbapenem was indicated in an alternative regimen in the presence of microbiological results or worsened or impaired patient status. Carbapenem was mainly used in combination regimens.